Klinično ovrednotenje intervencij farmacevta svetovalca v zdravljenju bolečine v ambulanti zdravstvenega doma pri starejših bolnikih s polifarmakoterapijo - Štuhec, Matej (Farmacevtski vestnik, 2018)
Pharmacotherapy review service provided by a pharmacist consultant is one of the possible approach in the pain pharmacotherapy optimization. Therefore, the main aim of this study was to determinate whether the involvement of pharmacist consultant directly into the patient nociceptive and neuropathic pain treatment process can improve the quality of drug prescribing in elderly patients treated with polypharmacy. Elderly patients from Community Health Centre Ljutomer were included in this retrospective study. Data on diagnoses, patient pharmacotherapy and pharmacist consultant`s interventions were obtained from patient`s medical documentation. 66 patients were included and pharmacist consultant suggested 27 different interventions and physicians accepted 16 different interventions (59.3%). The acceptance of pharmacist consultant recommendations had an influence on the better coherence with treatment guidelines. These results show that a collaborative care model including pharmacist consultant in pharmacotherapy review service had a significant impact on improving the quality of nociceptive and neuropathic pain pharmacotherapy in the primary care setting.
Keywords: clinical evaluation; community health centre; farmacevt svetovalec; klinično vrednotenje; nociceptive and neuropathic pain; nociceptivna in nevropatska bolečina; pharmacist consultant; retrospective study; retrospektivna raziskava; zdravstveni dom